Real-Time Video-assisted Intraoperative Neuromonitoring in Vestibular Schwannoma Surgery, 10-year Experience in a Referral Center of Excellence in Iran - Shahmohammadi, Mohammadreza; Zandpazandi, Sara; Behnaz, Faranak (Archives of Men’s Health, 2023)
Background: Vestibular schwannoma (VS) is an extra-axial, benign tumor mostly located in the cerebellopontine angle. The goal of VS surgery is gross total resection of the tumor along with preservation of the cranial nerves’ function. Intraoperative nerve monitoring is mainly rewarding in VS surgery. Method: This Cohort study was done retrospectively and prospectively from 2011-2021. Patients were divided into two groups; group one (n=19) underwent resection of the tumor with intraoperative neuromonitoring and group two underwent resection of the tumor without neuromonitoring based on patients’ ability to economically afford neuromonitoring. In the neuromonitoring group, Somatosensory Evoked Potential (SSEP) was evaluated and recorded throughout the whole surgery. Motor Evoked Potential (MEP) was recorded at regular intervals as well. We compared tumor size, hemorrhage volume during surgery, length of surgery, and facial nerve preservation (HB score), with one-year follow-up. Result: Facial nerve (FN) anatomical preservation rates were 100% and 75% in the neuromonitoring and control groups, respectively. The Gross Total Resection (GTR) rate in group one was 78.9%. The Subtotal Resection (STR) and Partial Resection (PR) rates in procedures without neuromonitoring were 50.0% and 12.5%, respectively. The House-Brackman (HB) level was good in all patients in group one, while 68.8% of patients in the control group had poor HB. Conclusion: Intraoperative Neuromonitoring (IONM) in VS surgery helps increase anatomical nerve preservation rate and FN outcome. The coordination of a anatomically trained neurophysiologist along with real-time video-assisted nerve monitoring avoids and lowers any delay in nerve recognition.